Manajemen Pembelajaran Ekstrakurikuler Matembang Sekar Madya di SMP Negeri 4 Sukawati untuk Melestarikan Karya Sastra Bali - Sustiawan, I Made Aris; Sustiawati, Ni Luh; Mawan, Gede (Institut Seni Indonesia Denpasar, 2025)
Purpose: This study aims to analyze the implementation of extracurricular learning of matembang sekar madya at SMP (Junior High School) Negeri 4 Sukawati and identify obstacles and strategies that can be applied to improve its effectiveness in preserving Balinese literary works. Research methods: It uses qualitative descriptive with data collection techniques through observation, interviews, and documentation. The subjects of the study consisted of extracurricular teachers, student participants in the activities, and the school. Results and discussion: Matembang sekar madya learning at SMP Negeri 4 Sukawati has been implemented systematically through a direct practice approach and guidance from expert teachers. There are several obstacles, such as lack of student interest, limited teaching resources, and minimal innovation in learning methods. Implication: With the right strategy, this extracurricular learning can be an effective means of preserving Balinese literary works while fostering students' love for regional cultural heritage.